(untitled) (Asian Journal of Pharmaceutics (AJP), 2018)
Precision medicine (PM) is an advanced high-model approach under which standard therapy for the right patient at an accurate time is provided, which is necessary for cancer therapy. Problems such as an individual diversity in gene, lifestyle, environment cause variability of the treatment response, and resistance to medication have been long-term challenges in oncology. Statics show that traditional clinical practices sometimes give poor health outcomes and a misuse of medical resources. In this model, a diagnostic is based on combined therapy using biomarker along with cellular, molecular, and genetic analysis. Diseases such as cancer including lung, breast, colorectal as well as leukemia, and melanomas can be controlled under this effective treatment by a physician to improve the chance of survival, reduce exposure to adverse effect, prevent harmful drug interaction, and increase overall efficacy. This revolutionized technology create a new era of medicine, in which researcher, health providers, and patient work together to improve health, treat diseases, and develop individualized care. Fighting against cancer is common to all countries. The GLOBOCAN statistics data revealed about 14.1 million newly diagnosed cancer patients, 32.6 million people living with cancer, and 8.2 million deaths from cancer worldwide. The cancer PM will hold advanced technology in other field including biotechnologies such as proteomics, next-generation sequencing, bioinformatics, and pharmacology to identify the actual cause for cancer and also tailor-fit personalized therapies.